Can somatic symptom disorder be an iatrogenic disease? - Mathilde Horn; Thomas Fovet; Vincent Sobanski; Ali Amad (BMC Psychiatry)
Abstract Background Somatic Symptom Disorder (SSD) is defined as persistent and clinically significant somatic symptoms accompanied by excessive and inappropriate health-related thoughts, feelings and behaviours. The causes of SSD are not fully understood, but the biopsychosocial model posits that they result from vulnerability to both precipitating and maintaining factors that contribute to the progression of symptoms from short-term/acute distress presentation to a more persistent and even disabling problem. Case presentation We report the case of a patient who developed a SSD after a prolonged period of medical care that ultimately led to the diagnosis of pheochromocytoma. After surgery (that should have resolved the initially-presenting problem), both physical symptoms and distress persisted, suggesting that SSD was present and remained even after treatment of the original/underlying physical symptom profile. Conclusions This case report emphasizes the importance of early diagnosis of SSD when a patient presents with excessive health-related thoughts or behaviors, and not only after physical diagnoses have been ruled out. Based on the predictive model of SSD, early SSD treatment may help to reduce physical symptoms, regardless of their etiology. Diagnosing SSD and investigating the potential etiology of physical symptoms should be seen as complementary approaches, rather than opposing ones.